Complete genome sequence of 'Thermobaculum terrenum' type strain (YNP1T). Issue 2 (September 2010) - Kiss, Hajnalka; Cleland, David; Lapidus, Alla; Lucas, Susan; Glavina Del Rio, Tijana; Nolan, Matt; Tice, Hope; Han, Cliff; Goodwin, Lynne; Pitluck, Sam; Liolios, Konstantinos; Ivanova, Natalia; et al.
Abstract 'Thermobaculum terrenum ' Boteroet al. 2004 is the sole species within the proposed genus 'Thermobaculum '. Strain YNP1T is the only cultivated member of an acid tolerant, extremely thermophilic species belonging to a phylogenetically isolated environmental clone group within the phylumChloroflexi . At present, the name 'Thermobaculum terrenum ' is not yet validly published as it contravenes Rule 30 (3a) of the Bacteriological Code. The bacterium was isolated from a slightly acidic extreme thermal soil in Yellowstone National Park, Wyoming (USA). Depending on its final taxonomic allocation, this is likely to be the third completed genome sequence of a member of the classThermomicrobia and the seventh type strain genome from the phylumChloroflexi . The 3, 101, 581 bp long genome with its 2, 872 protein-coding and 58 RNA genes is a part of theG enomic E ncyclopedia of B acteria and A rchaea project.